2011
DOI: 10.1007/s00467-011-2001-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of circulating fibroblast growth factor-2 in lipopolysaccharide-induced acute kidney injury in mice

Abstract: Background Fibroblast Growth Factor (FGF-2) is an angiogenic growth factor involved in renal growth and regeneration. Previous studies in rodents showed that single intrarenal injections of FGF-2 improved the outcome of acute kidney injury (AKI). Septic children usually show elevated plasma levels of FGF-2, and are at risk of developing AKI. However, the role of circulating FGF-2 in the pathogenesis of AKI is not well understood. Methods Here, we developed a mouse model to determine how FGF-2 released into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…This is consistent with our previous findings showing elevated urinary levels of FGF-2 in children with classic and atypical forms of HUS [44, 56]. Other studies done in different rodent models of acute kidney injury induced by renal ischemia [34, 35] or lipopolysaccharide injections [36, 37] also support the notion that FGF-2 plays a critical role in the outcome of AKI. In our study, FGF-2 was not as sensitive as urinary NGAL to detect AKI in critically ill children; however, the use of both biomarkers combined improved the specificity of this test to identify AKI, relative to the use of each biomarker alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with our previous findings showing elevated urinary levels of FGF-2 in children with classic and atypical forms of HUS [44, 56]. Other studies done in different rodent models of acute kidney injury induced by renal ischemia [34, 35] or lipopolysaccharide injections [36, 37] also support the notion that FGF-2 plays a critical role in the outcome of AKI. In our study, FGF-2 was not as sensitive as urinary NGAL to detect AKI in critically ill children; however, the use of both biomarkers combined improved the specificity of this test to identify AKI, relative to the use of each biomarker alone.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the release of angiogenic factors in the plasma of critically ill children can be associated with a worse clinical outcome [31]. Furthermore, studies done in experimental animal models of AKI induced by renal ischemia [34, 35] or lipopolysaccharide injections [36, 37], have shown that the administration of angiogenic factors, such as fibroblast growth factor −2 (FGF-2), can affect the outcome of AKI. In addition, previous studies have shown that the urinary levels of epidermal growth factor (EGF) can been used to predict and/or monitor the outcome of AKI, both in children [3840] and adults [41].…”
Section: Introductionmentioning
confidence: 99%
“…In this experimental adult mouse model, 38,39 only the hepatocytes are infected with the adenoviral vectors, and FGF-2 released into the circulation is trapped in the kidney bound to HSPGs. 13,15,16,36,40 As shown in Figure 8, FGF-2 increased the renal expression of pERK, Rho-A, pMLC 2 , and MMP-9 in both WT and HIV-Tg 26 mice.…”
Section: Arginines In the Tat Basic Domain Sequences Mediate Lr Assocmentioning
confidence: 99%
“…In other experiments, WT or HIV-Tg 26 adult male mice without preexisting renal disease were divided in two groups (n=3-5 mice per group) and injected through the retro-orbital vein plexus with adenoviral vectors carrying LacZ or a 700-bp cDNA sequence encoding a secreted form of human FGF-2 (rAd-FGF-2; 5310 8 pfu/mouse) as previously described. 38,69,70 Mice were euthanized 7 or 28 days after the adenoviral infection, and their kidneys were processed for signaling or renal histologic studies as described above. Renal injury was assessed in sections stained with period acid-Schiff by counting the percentage of glomeruli exhibiting segmental/global sclerosis and the percentage of tubular casts and microcysts.…”
Section: Studies In Wt and Hiv-tg 26 Micementioning
confidence: 99%
See 1 more Smart Citation